ROMAN SPECTACLES BUILDINGS AS A SETTING FOR MARTYRDOM AND ITS CONSEQUENCES IN THE CHRISTIAN ARCHITECTURE - Jordina Sales Carbonell (Journal of Ancient History and Archaeology)
In the framework of the study of Christian buildings in the ruins of amphitheaters, theaters, stadiums and Roman circuses, becomes appropriate to develop some reflections mainly aimed helping to explain the symbolic dimension acquired by the ludic background in which a far from negligible part of the Christian martyrdoms took place, as outlined on the preserved sources. Although this ludic substrate is not the only factor to be considered, it’s the one that allowed the hagiographers composing stories —some with more historical veracity than others— with architectural settings charged with symbolism, where the victory of the martyrs as “athletes of Christ” was equated to the victory in secular games. All this greatly contributes to explain the subsequent relationship between Christian building and playful architecture occurred from the late fourth and early fifth century, and detected in the late antique and early medieval topography of some Roman cities. However, this issue has gone relatively unnoticed for Archeology, and when the two key elements —building and church— appear, with few exceptions, they are considered separately in case of being subjected to some kind of study.